Faktor yang Mempengaruhi Pemanfaatan Layanan Jamkesta oleh Rumah Tangga di RS dr. Ainun Habibie - Lakadjo, Rasmin; Yusuf, Barmin Rahmat A.G; Yakup, Anggita Permata; Ibrahim, Ismail A. (Universitas Negeri Surabaya, 2025)
The Universal Health Protection Program (Jamkesta) in Gorontalo Province aims to expand healthcare access for low-income households, yet its utilization remains uneven across demographic groups. This study examines the factors influencing the use of Jamkesta healthcare services among households seeking care at dr. Ainun Habibie Hospital. Using a quantitative explanatory design with 200 respondents, the study employs a logistic regression model to assess the roles of predisposing, enabling, and need factors in shaping healthcare utilization. The results indicate that age, access to village-level health facilities, and membership in community organizations significantly influence the likelihood of using Jamkesta services. In contrast, gender, educational attainment, employment status, and household size do not show significant effects. These findings highlight the importance of accessibility and social networks in driving healthcare utilization, suggesting the need for strengthened health literacy, equitable information dissemination, and improved service quality to ensure that Jamkesta functions effectively as an inclusive public health protection mechanism.